2002
DOI: 10.1161/01.cir.0000027567.49283.ff
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lipid-Lowering Therapy on the Progression of Coronary Artery Calcification

Abstract: Background-Coronary calcification measured by fast computed tomography techniques is a surrogate marker of coronary atherosclerotic plaque burden. In a cohort study, we prospectively investigated whether lipid-lowering therapy with a cholesterol synthesis enzyme inhibitor reduces the progression of coronary calcification. Methods and Results-In 66 patients with coronary calcifications in electron beam tomography (EBT), LDL cholesterol Ͼ130 mg/dL, and no lipid-lowering treatment, the EBT scan was repeated after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
165
4
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(183 citation statements)
references
References 35 publications
7
165
4
7
Order By: Relevance
“…In addition to phosphate, inflammatory cytokines, and oxidative stress, several in vitro and clinical studies have shown lipids to play a crucial role in the pathogenesis of vascular calcification. Lipid-lowering drugs including statins are in fact effective in reducing vascular calcification in several clinical trials (7)(8)(9). In vascular calcification, n-3 unsaturated fatty acids play a protective role through a p38-MAPK (mitogen-activated protein kinase)-dependent mechanism, whereas oxidized lipids such as oxysterols and oxidized phospholipids elicit procalcific effects in vascular cells.…”
mentioning
confidence: 99%
“…In addition to phosphate, inflammatory cytokines, and oxidative stress, several in vitro and clinical studies have shown lipids to play a crucial role in the pathogenesis of vascular calcification. Lipid-lowering drugs including statins are in fact effective in reducing vascular calcification in several clinical trials (7)(8)(9). In vascular calcification, n-3 unsaturated fatty acids play a protective role through a p38-MAPK (mitogen-activated protein kinase)-dependent mechanism, whereas oxidized lipids such as oxysterols and oxidized phospholipids elicit procalcific effects in vascular cells.…”
mentioning
confidence: 99%
“…4 -7 During the past several years, coronary artery calcium (CAC) measured by electron beam tomography (EBT) has evolved into a useful tool for risk prediction, 8 -12 and monitoring of CAC progression over time has been proposed as a tool to follow the evolution of the atherosclerotic plaque burden. 13,14 To further support the utility of this tool, initial evidence indicates that progression of CAC is linked to an unfavorable prognosis. 15,16 In this retrospective study, we reviewed the data collected in 1310 individuals submitted to sequential EBT scanning, 157 of whom were affected by diabetes, to assess the difference in plaque burden growth in patients with and without diabetes mellitus.…”
mentioning
confidence: 99%
“…In a study of 66 subjects who were followed during a periods without statin treatment and then during treatment with cerivastatin 0.3 mg p.o. qd, the overall median annualized relative change was significantly higher in the untreated interval compared with the treated interval (25% vs 8.8%, P< 0.0001) 51 . The annualized relative change of the CAC score in 32 patients who achieved an LDL-C level of < 100 mg/dL decreased from 27% to -3.4% (P< 0.0001).…”
Section: Coronary Calcificationmentioning
confidence: 86%